Impact of the Project P.A.T.H.S. in the Junior Secondary School Years: Individual Growth Curve Analyses - Daniel T. L. Shek; Cecilia M. S. Ma (The Scientific World Journal)
The Tier 1 Program of the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programs) is a positive youth development program implemented in school settings utilizing a curricular-based approach. In the third year of the Full Implementation Phase, 19 experimental schools (n = 3,006 students) and 24 control schools (n = 3,727 students) participated in a randomized group trial. Analyses based on linear mixed models via SPSS showed that participants in the experimental schools displayed better positive youth development than did participants in the control schools based on different indicators derived from the Chinese Positive Youth Development Scale, including positive self-identity, prosocial behavior, and general positive youth development attributes. Differences between experimental and control participants were also found when students who joined the Tier 1 Program and perceived the program to be beneficial were employed as participants of the experimental schools. The present findings strongly suggest that the Project P.A.T.H.S. is making an important positive impact for junior secondary school students in Hong Kong.